Endoscopic laser palliation for advanced malignant dysphagia. Issue 7 (July 1987) - Bown, S G; Hawes, R; Matthewson, K; Swain, C P; Barr, H; Boulos, P B; Clark, C G
Abstract : Palliative treatment of malignant dysphagia aims to optimise swallowing for the maximum time possible with the minimum of general distress to these seriously ill patients. Thirty four patients considered unsuitable for surgery because of advanced malignancy, other major pathology or in whom previous surgery had been unsuccessful were treated endoscopically with the Nd YAG laser. Significant improvement was achieved in 29 (85%). On a scale of 0-4 (0 = normal swallowing; 4 = dysphagia for all fluids), mean improvement was 1.7, with 25 patients (74%) able to swallow most, or all solids after treatment. With increasing experience, the average number of treatment sessions required for each patient became less; initial time in hospital became comparable to that needed for intubation. Failures were caused by inappropriate patient selection (3), or laser related perforation (2). The mean survival in the whole group was 19 weeks (range 2-44). Eighteen patients needed further treatment for recurrent dysphagia, a mean of six weeks (range 2-15) after initial therapy. Ten of these responded, but eight eventually required insertion of a prosthetic tube. The duration of good palliation was very variable after initial laser therapy.